Study on the association between pregnancy-associated plasma protein-A and acute cerebral infarction - Zheng, Sihang; Hossain, Mohammad Showkat; Wu, Hongliang; Nao, Jianfei (Frontiers in Neurology, 2023)
Objective We aimed to study the correlation between pregnancy-associated plasma protein-A (PAPP-A) and acute cerebral infarction (ACI). Methods Patients who had the symptoms of paralysis, aphasia, or sudden neurological impairment from June 2020 to October 2021 were chosen. There were 159 patients diagnosed with ACI as the experimental group and 102 patients without ACI as the control group. We collected clinical data and observed whether they have a certain impact on plasma PAPP-A levels. The ACI group was divided into two groups: mild neurological deficit group (NIHSS score < 3) and moderate and severe neurological deficit group (NIHSS score > 3). The ACI group was divided into the atherosclerotic-type group and the arteriolar occlusion-type group according to the TOAST classification. The ACI group was divided into a good prognosis group (mRS ≤ 2 points) and a poor prognosis group (mRS > 2 points) using the Modified Rankin Scale (mRS) for 90 days of follow-up. Plasma PAPP-A levels were compared between those groups. Results (1) The plasma PAPP-A level in patients with ACI (1.840 ± 0.281) was significantly higher than that in the control group (1.690 ± 0.260). Smoking history, leukocyte count, cystatin C, homocysteine, and plasma PAPP-A levels were independently correlated with ACI. (2) The level of PAPP-A in patients with moderate and severe neurological impairment was lower than that in patients with mild neurological impairment. (3) The level of PAPP-A in patients in the arteriolar occlusion-type group was higher than that in patients in the atherosclerosis-type group. (4) The PAPP-A levels in the group with elevated low-density lipoprotein are higher than those in the group with normal low-density lipoprotein. (5) Plasma PAPP-A level was not correlated with infarction location, infarction volume, or prognosis at the 90-day follow-up. Conclusion (1) The level of plasma PAPP-A could be the independent risk factor of ACI. It is positively correlated with triglyceride and cholesterol content. (2) PAPP-A level is positively correlated with low-density lipoprotein. (3) PAPP-A levels between different disease severities have a significant difference. (4) The level of plasma PAPP-A in the arteriolar occlusion-type group was higher than that in the atherosclerotic-type group.